Analisis Faktor Yang Berhubungan Dengan Kepatuhan Penggunaan Alat Pelindung Diri Di Masa Pandemi COVID-19 Pada Tenaga Kesehatan - Evrin Angga; Indasah Indasah (Jurnal Keperawatan Muhammadiyah, 2022)
Compliance of health workers using Personal Protective Equipment (PPE) in the current pandemic conditions is more important to pay attention to because negligence in its use can endanger their safety. In fact, there are still many health workers who do not comply in using PPE according to predetermined standards. The study aims to determine the relationship between knowledge factors, attitudes towards the use of PPE and the availability of PPE with the compliance of health workers in the use of PPE in the Inpatient Installation of Kanjuruhan Hospital, Malang Regency. The study is correlational in design with a cross-sectional approach. The population of all health workers at the Wonosari Health Center, Kepanjen and Ngajum, Malang Regency, who focus on handling COVID-19. Determination of sample members using simple random sampling technique, a sample of 73 respondents. Data collection using questionnaire instruments, and data analysis using the Spearman test. Spearman's test results showed that there was a relationship between knowledge factors (p= 0.000,= 0.491), attitudes towards the use of PPE (p= 0.000, = 0.705), and the availability of PPE (p = 0.000, = 0.763) with the compliance of health workers in the use of PPE. Knowledge is related to compliance with the use of PPE because with good knowledge, health workers will increasingly realize the importance of using PPE for their safety. The attitude related to compliance with the use of PPE because of the positive attitude of health workers towards the importance of using PPE, is a situation where health workers view the use of PPE as an important thing to implement for their own safety, causing a tendency to behave towards compliance in the use of PPE. The availability of PPE is related to compliance with the use of PPE because to be able to comply with the use of PPE, of course, health workers need adequate facilities.